The Implementation of Herringbone Pattern in Improving Students' Reading Comprehension - Abdullah Syukur; Ardhy Supraba; Edi Wahyono (Universitas Muhammadiyah Enrekang, 2020)
This research aimed at finding out the effectiveness of Herringbone Technique in improving students’ reading comprehension at the fifth semester student of Informatics Study Program Faculty of Computer Engineering Cokroaminoto Palopo University. This research applied a pre-experimental method with one group pre-test and post-test. The population of this research was the fifth semester student of Informatics Study Program Faculty of Computer Engineering Cokroaminoto Palopo University. The sample of this research was class 5A consisted of 40 students, the sample was taken by using random sampling technique. There are two kinds of instrument used in this research, namely test and questionnaire. The result of the research shows that the reading comprehension ability of the fifth semester student of Informatics Study Program Faculty of Computer Engineering Cokroaminoto Palopo University was very effective. It was proven by the mean score in post-test was 7.55 and the T-test value 43.375 which was higher than the T-table value 2.315. And the students were interested in learning reading comprehension using Herringbone technique.